Spatial and temporal threat of slope failures in the Klang Valley region,Malaysia - Khairulmaini, O.S.; Thanapackiam, P.; Fauza, A.G. (shankargargh.org, 2012)
Slope failures intensity and frequency had increased in the last decade. This study examines the trend change form of slope failures and the directional spatial tendency of slope failures in the last decade in the Klang Valley Region (KVR) of Malaysia. The temporal and spatial changes have great significance on population vulnerability in the KVR. Two significant effects identified are first the increasing intensity - frequency impact of slope failures on KVR population and secondly the spatial direction of the impacts in the KVR. Both of these effects create severe stresses on the population of the KVR. The study observed that the temporal and spatial advances of slope failures would continue to increase in intensity and frequency in the not so distant future as the environment would become more stressful as a result of urbanization.